Perbedaan Hasil Belajar Dengan Menggunakan Model Pembelajaran 5E dan Generative Learning Di Kelas XI MIPA SMA Negeri 7 Banjarmasin - Bastomi Saputra; Syubhan Annur; Mastuang Mastuang (Berkala Ilmiah Pendidikan Fisika, 2017)
The background of this research is because 79,33% of students of class XI MIPA SMA Negeri 7 Banjarmasin have not reached the value of completeness in Middle Semester test. This is because students tend to memorize the concept, but do not know how the concept is obtained, and not able to apply the concept in a new situation. This study aims to analyze differences in learning outcomes by using the 5E learning model and Generative Learning in class XI MIPA SMA Negeri 7 Banjarmasin. This research is a quasi-experimental research with nonequivalent group pretest-posttest design. Sampling using cluster random sampling technique. Based on the technique, obtained sample that is class XI MIPA 2 and XI MIPA 4. Instrument of this research is test result of learning, that is pretest and postest. Data analysis technique using t-test. The results showed that there are differences in learning outcomes of learners between the 5E learning model and Generative Learning.